Study on the responses of glutathione S-transferase Acidovorax sp. KKS102 towards antibiotics / Rosalia Rani - Rosalia , Rani (2022)
Beta class glutathione S-transferase (GST) activity is known to be associated with antibiotic resistance, one of the most serious threats to global health. In this research, the study of antibiotic resistance developed by beta class GST was conducted using KKSG6, one of the GST isozymes found in Acidovorax sp. KKS102. The KKSG6 gene has been successfully expressed in Escherichia coli BL21 Star™ (DE3) using pET101/D-TOPO®-KKSG6 as an expression vector, resulting in the presence of a protein band around 20 kDa. KKSG6 protein has also been successfully purified using GSTrap™ HP column. Optimisation expression showed that KKSG6 exhibits its optimum activity when the culture was incubated 5 hours after the addition of 0.1 mM IPTG. Over-expression of KKSG6 made Escherichia coli BL21 Star™ (DE3) to be less susceptible towards kanamycin, streptomycin, gentamycin, tetracycline and chloramphenicol, suggesting the antibiotics binding with KKSG6. Our study has shown that chloramphenicol inhibited the conjugation activity of the enzyme towards CDNB. An in-silico study using protein-ligand docking predicted that antibiotics binding could take place at the protein dimer interface and H-site depending on their properties.